“Gebyar Literasi” Apresiasi Tingkat Desa Ulu Pulau, Kecamatan Bantan, Kabupaten Bengkalis - Nur Asiah; Aldo Pahripal; Dhea Imanuella Violyn; Hafael Bernanza; Jamiatul Kevin Permana; M. Nurcholis Syaefuzi; Muhammad Rais; Neshy Muliana; Putri Adhelin; Ridho Permana; Yohana Sinaga; Yunia Tasya (Unri Conference Series: Community Engagement, 2025)
The “Gebyar Literasi, Apresiasi Tingkat Desa” program conducted in Ulu Pulau Village is one of the work programs of the UNRI 2025 Thematic Literacy Community Service Program (KKN) based on the Sustainable Development Goals (SDGs), with a focus on SDG 4, Quality Education. This program has several competition categories, namely Book Review Competition, Reading Aloud Competition, and Coloring Competition. The aim of this activity is to enhance literacy skills, including the ability to understand, interpret, and effectively communicate the content of readings in an engaging manner. It also aims to develop speaking skills, particularly in terms of pronunciation, intonation, expression, and confidence when speaking in public. It also seeks to develop creativity, imagination, and fine motor skills through visual expression (coloring). Additionally, it aims to foster a love for reading, appreciation for art, and self-confidence among participants. The program also trains participants in attention to detail, concentration, and analytical skills across all aspects of reading, reviewing, and creating. This program was initially taught at schools over several days, with the book review category participated in by students in grades 4-6, the reading aloud category by students in grades 2–3, and the coloring category by students in grade 1 and preschool/kindergarten. The results of the activities showed an increase in interest in learning and literacy comprehension, fostering a greater interest in reading. In addition, the program also succeeded in building emotional closeness between university students and school students, as well as encouraging the growth of a culture of learning within families and communities. These activities are concrete evidence of the role of Riau University students in promoting inclusive and quality education in rural areas, in line with the spirit of SDG 4.